Cities and National and Religious Structures of Khorasan Region in the 4th and 5th Centuries (10th and 11th AD) - رشید, کامل حبیب; عثمان, شوان (Sulaimani Journal for Humanities, 2020)
The purpose of this research titled (The cities of Khorasan Region and its ethnicity and religions) is to collect information on the region of Khorasan and its four famous cities along with the ethnic and religious groups this region has had. The benefit of this research is evident in revealing to readers and people in power the history of the region and its urbanization with the aim of enriching their knowledge. The research contains four sections one of which includes an opening to introduce the Region of Khorasan during the fourth and fifth century of the Islamic Calendar (equivalent with the tenth and eleventh of the Gregorian calendar),The second section is to introduce the important cities of Khorasan in which we have talked of all four important cities of Khorasan (Naysabur, Balkh, Marv, and Herat). The third section is dedicated to explaining the ethnicity of the region in which the crucial ethnic groups are introduced. The fourth and last section is a description of various religions of the region. In this section it will be found that this region is home for a numerous world religions. At the end of the research, we have shown some conclusions we have reached along with granting credit to all used sources.